Historical narrative of Hayden White in research on the history of law - Gaczoł, Klaudia (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The aim of the article is to try to answer the question whether narrative issues can be found in historical and legal research and – as a consequence – in the analysis of the current law. The starting point will be the theory of historical writing proposed by Hayden White. According to White, each historical manifesto is burdened with specific strategies of explanation, which the historian uses to interpret and explain past events. Historical discourse appears as a coherent history, which is built using ideology. Hayden White, just like Paul Ricoeur, is convinced that the foundation of such a constructed narrative is in fact metaphorical. The peculiarity of the methods used by historical and legal sciences lies in the fact that they combine two types of the methodological directives – the directives of historical sciences and the directives of legal sciences. Therefore, it is necessary to consider the ideological aspect of research, which inevitably distorts the result of the historian's work and, as a result, the dogmatics of law. In historical and legal research, however, we can identify the ideological aspect in the narrative, hidden at the presupposition level of the legal text. Thus, the impact of such a constructed history on the law-making procedures is not without significance, as can be seen in the ways of preserving historical memory in the generally applicable legal acts.
Keywords: Hayden White; historical narrativism; historical writing; history of law; methodology